English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3: x2 + 5x + 4 = 0
4, 1/4
-1, -4
-4, 1

10: 33x² - x - 14 = 0
2/3, -7/11
3/2, -7/11
2/3, 7


11: 21x² + 22x - 24 = 0
-4/3, 5/7
-2/3, -12/7
2/3, -12/7


12: 2x2 + 2x = 60
5, -6
6, -5
-3, 5


13: x2 + 16x + 48 = 0
-3, 4
4, 12
-4, -12


14: x3 - x2 - 12x = 0
-3, 4, 0
2, 4, 6
-2, 3, 0

2007-03-31 07:51:22 · 3 answers · asked by *MaRiSsA* 2 in Science & Mathematics Mathematics

3 answers

3) factor to get: (x+4)(x+1)=0 so x=-4 or -1
10) (11x+7)(3x -2 ) so x=-7/11 and x=2/3
11) (7x +12)(3x -2)=0 so x=-12/7 and x=2/3
12) (x +6 )(x -5 ) so x=-6, 5
13) (x+12)(x+4) x=-12, -4
14) x(x-4)(x+3) x=0,4,-3

2007-03-31 08:02:22 · answer #1 · answered by bruinfan 7 · 0 2

3: x2 + 5x + 4 = (x+1)(x+4) --> x = -1 and -4

10: 33x² - x - 14 = 0 =(3x-2)(11x+7) --> x= 2/3 and -7/11

11: 21x² + 22x - 24 = 0=(3x-2)(7x+12)--> x=2/3 and x= -12/7

12: 2x2 + 2x = 60
x^2+x-30=0 = (x+6)(x-5) --> x = -6 and x = 5

13: x2 + 16x + 48 = 0=(x+4)(x+12) --> x=-4 and x=-12

14: x3 - x2 - 12x = 0
=x(x^2-x-12) = x(x-4)(x+3) --> x =0 and x = 4 and x = -3

2007-03-31 08:14:51 · answer #2 · answered by ironduke8159 7 · 0 0

1) x^2+4x+x+4=0
(x+1)(x+4)=0. ans.x= -1,-4
2)33x^2-22x+21x-14=0
11x(3x-2)+7(3x-2)=0
x= -7/11, 2/3
3)21x^2+36x-14x-24=0
3x(7x-12)+2(7x-12)=0
x=-2/3 , 12/7
4)2x^2+12x-10x-60=0
2x(x+6)-10(x+6)=0
x=5,-6
5)x^2+12x+4x+48=0
(x+12)(x+4)
x=-12,-4
6)x(x^2-x-12)=0
x=0 & x^2-4x+3x-12=0
x=0,4,-3

2007-03-31 08:24:57 · answer #3 · answered by SS 2 · 0 0

fedest.com, questions and answers